2021
DOI: 10.3390/biology10101010
|View full text |Cite
|
Sign up to set email alerts
|

Attraction to Smelly Food in Birds: Insectivorous Birds Discriminate between the Pheromones of Their Prey and Those of Non-Prey Insects

Abstract: Natural selection has favored the evolution of different capabilities that allow animals to obtain food—e.g., the development of senses for improving prey/food detection. Among these senses, chemical sense is possibly the most ancient mechanism used by organisms for environmental assessment. Comparative studies suggest the prime role of foraging ecology in the evolution of the olfactory apparatus of vertebrates, including birds. Here, we review empirical studies that have shown birds’ abilities to detect prey/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…However, in the current study we had an unexpected result, as we did not find any caterpillars being attacked by avian predators. The use of similar artificial larvae for estimating bird attraction to trees has been used successfully in several studies [ 24 , 31 , 36 , 40 , 41 , 42 , 43 , 44 , 45 ], even within the same bird population [ 46 ]. Therefore, the lack of attraction even to Herbivore-infected trees is unlikely due to the use of artificial caterpillars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the current study we had an unexpected result, as we did not find any caterpillars being attacked by avian predators. The use of similar artificial larvae for estimating bird attraction to trees has been used successfully in several studies [ 24 , 31 , 36 , 40 , 41 , 42 , 43 , 44 , 45 ], even within the same bird population [ 46 ]. Therefore, the lack of attraction even to Herbivore-infected trees is unlikely due to the use of artificial caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the attraction of birds to each tree by checking the number of plasticine larvae with marks indicating predation by birds. This method has been used in previous studies of avian predation [ 24 , 31 , 35 , 36 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The artificial larvae are considered damaged when they had triangle-shaped marks and deep cuts made by bird beaks and when a part of their body was taken by the birds (see [ 24 , 35 ]).…”
Section: Methodsmentioning
confidence: 99%
“…The use of similar artificial larvae for estimating bird attraction to trees has been used successfully in several studies [24,31,36,[40][41][42][43][44][45]. Even the results of a previous study in the same population of birds using artificial caterpillars of similar shape and coloration [46] showed that birds were attacking them. Therefore, the lack of attraction to even to Herbivore-infected trees is unlikely to be due to the use of artificial caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the attraction of birds to each tree by checking the number of plasticine larvae with marks indicating predation by birds. This method has been used in previous studies of avian predation [24,31,35,36,[40][41][42][43][44][45][46]. The artificial larvae are considered damaged when they had triangle-shaped marks and deep cuts made by the beak of the birds and when a part of their body was taken by the birds (see [24,35]).…”
Section: Experimental Designmentioning
confidence: 99%
“…Other vertebrate predators have long been known to use odor cues to find prey (Conover 2007, Gardiner and Atema 2007, Johannesen et al 2012. Recent work has shown that birds can also locate prey directly via odor cues (Nevitt 2000, Cunningham et al 2008, Saavedra and Amo 2018a, Amo and Saavedra 2021, Díaz-Siefer et al 2021. Predation on herbivorous insects is well known to be governed by tritrophic interactions mediated by the release of herbivore induced plant volatiles (HIPVs) upon plant wounding (D' Alessandro and Turlings 2006, Heil 2008, Arimura et al 2009, Kaplan 2012.…”
mentioning
confidence: 99%